EDUCATION QUALITY ASSURANCE - (Boonprom Carupuñño), Phrametheepariyatthada; Siriwatcharaworakun, PhramhaSiriwattana; Tanawutpornpinit, SiriKarn; Changcharoen, Chompoonuch (Journal of Educational Review Faculty of Education in MCU, 2021)
This article aims to propose the subject of educational quality assurance, and to create knowledge and understanding for school administrators, teacher and educational personnel lead the practice of educational management towards desirable goals of improving educational quality of the country. At present, human resources are the most important factor in the development of the country. The quality of education therefore reflects the quality of the people who are the product of education management.Educational institutions can provide educational quality according to educational standards and achieve the goals of the agency or regulatory agency. Educational institutions must have operational processes to generate confidence, operational planning process standards are set for implementation according to planned plans and established standards. It is also reviewed to ensure that the organization's products and services satisfy to meet the specified quality standards both in terms of educational excellence and in terms of efficiency of educational system administration that all parties must help each other to develop smoothly, efficiently and effectively.